Research on the network handoff strategy based on the best access point name decision - Shu, Zhong; Shu, Ya-Jie; Zhang, Qian; Ye, Hui-Rong (Frontiers in Computational Neuroscience, 2023)
In order to improve the network switching performance and efficiency of mobile phone terminals and establish an efficient mobile communication network connection, this paper constructs the SDN+MPTCP+CP (Software Defined Network and MultiPath TCP and Mobile Terminal) mobile communication network model and designs a network switching algorithm with preselected available APN (Access Point Name) access points based on potential game. The constructed network model integrates a 5G mobile communication network, satellite communication, SDN network, and MPTCP multi-way communication technology. APN access point is preselected using Kalman filtering theory, and dual problems are solved with Lagrangian. In order to determine the MPTCP sub-flow transmission path, the differential derivative calculation is introduced. The network switching strategy performance is evaluated based on the Jacobian matrix. Then, the game coefficient is designed, and the game function is calculated. A potential game balance point is found, and an updating strategy is formulated to determine the best APN access point. The simulation network model is constructed, and the performance evaluation parameters are defined to evaluate the performance comprehensively. The experimental results demonstrated the proposed algorithm's extreme reliability, stability, and compatibility.